Reflections from the Dassler Cabin - Freeman, Glenn (The Trumpeter, 2016)
This essay is a narrative account of my experience as an artist-in-residence on Isle Royale national park. The essay considers the implications of "rewilding" and the importance of human history as part of our wilderness environments.